ANALYSIS OF BUSINESS EFFICIENCY AND LOCAL CHICKEN PRODUCTION FACTORS IN WEST JAVA - Wendry Setiyadi, Taslim, Sjafril Darana (International Journal of Advanced Science and Technology, 2020)
The study aims to determine the level of business efficiency and factors that influence local chicken production. This research was carried out at a local chicken farm belonging to Mekar Jaya Farmer group members, Dawuan Kaler Village, Dauwan District, Subang Regency, West Java Province with a total sample of 32 farmers in March 2019. The method used was a survey. The data used consists of primary and secondary data. Data obtained through interviews with the Mekar Jaya herd group. The analytical tool used is the analysis of the level of efficiency and multiple linear regression test. The results of the efficiency analysis show that, all livestock production efforts are efficient R / C> 1 with an average level of efficiency of 1.67. Efficient breeders are above the average of 16 breeders (50%), below the average efficient 15 breeders (47%) and equal to an average of 1 breeders (3%) in conducting local chicken businesses. For the multiple linear regression test, the results show that simultaneously the results of local chicken production with a significance value <α = 0.05 and Fcount = 18.29. The factor of chicken ration price (-3.65), DOC seed price (-1.69) and mortality (-0.28) have a negative and partially significant effect on production yield. Factors of live chicken prices (3.83) have a positive and partially significant effect on production results.